1986
DOI: 10.1039/p19860002021
|View full text |Cite
|
Sign up to set email alerts
|

Aroylation of carbanions derived from N-(diphenylmethyl)arylmethanimines. A synthesis of 4-aroyloxy-2-azabuta-1,3-dienes

Abstract: The acylation of carbanions derived from N-(diphenylmethyl)arylmethanimines using aroyl chlorides, allows the preparation of a new type of substituted 2-azabuta-l,3-dienes in which the imino group is conjugated with an enol ester. The reaction is quite general and facilitates the preparation of a wide range of 2-azadienes with electron-donating and electron-withdrawing groups on the phenyl rings. The site selectivity for the attack of the electrophile on the aza-ally1 anion can be controlled by the substituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…132-134 8C (lit. [18] N-Butylidene-1,1-diphenylmethanamine (9 j): [7a] Crude product obtained as a light yellow oil in 74 % yield. N-(Cyclohexylmethylene)-1,1-diphenylmethanamine (9 k): [19] Recrystallization (ethyl acetate/hexanes 1:5) afforded 9 k in 74 % isolated yield as an off-white solid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…132-134 8C (lit. [18] N-Butylidene-1,1-diphenylmethanamine (9 j): [7a] Crude product obtained as a light yellow oil in 74 % yield. N-(Cyclohexylmethylene)-1,1-diphenylmethanamine (9 k): [19] Recrystallization (ethyl acetate/hexanes 1:5) afforded 9 k in 74 % isolated yield as an off-white solid.…”
Section: Methodsmentioning
confidence: 99%
“…VAPOL and VANOL were purified by column chromatography with 3:1 hexanes/dichloromethane. All aldimines were synthesized by a known procedure [18] and purified by recrystallization from hexanes or from a mixture of hexanes/ethyl acetate. Aziridines were purified by column chromatography with hexanes/ethyl acetate and further purified by recrystallization from hexanes/ethyl acetate if needed.…”
Section: Methodsmentioning
confidence: 99%
“…N-Benzyl-1,1-diphenylmethanimine (3ea). 20 Colorless solid, 37.9 mg, 70%, mp 54−57 °C; 1 H NMR (400 MHz, CDCl 3 ): δ 7.72 −7.66 (m, 2H), 7.55−7.11 (m, 13H) (1E,2E)-N 1 ,N 2 -Bis(2,6-dimethylphenyl)-1,2-diphenylethane-1,2diimine (4ea). 6 White solid, 7.8 mg, 20%; 1 H NMR (400 MHz, CDCl 3 ): δ 7.88 4H),16H),4.6 (d,J = 15.9 Hz,2H),4.53 (d,J = 15.9 Hz, 2H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ): δ 166.0, 139.…”
Section: Scheme 2 Control Experimentsmentioning
confidence: 99%
“…In the course of our investigations, we have found that GaI can be used as a Lewis acid catalyst for the Schiff base condensation of a primary amine and a ketone. The Schiff base condensation reaction of an aldehyde or ketone with an amine is well known to be catalyzed by Lewis acids (Armesto et al, 1986). The addition of 2,6-diisopropylaniline to a suspension of GaI in toluene, followed by half an equivalent of acetone gives rise to the expected condensation product, (I).…”
Section: Figurementioning
confidence: 99%